PERBANDINGAN KEMAMPUAN MENGHAFAL AL-QUR’AN ANTARA SISWA YANG MENGIKUTI PROGRAM TAKHASSUS DENGAN YANG TIDAK MENGIKUTI PROGRAM TAKHASSUS DI MADRASAH TSANAWIYAH NEGERI 2 PONTIANAK TAHUN 2025-2026 - Kamala, Kiki; Alias, M.; Wahdah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Takhassus Al-Qur'an Program is one of the flagship programs designed to improve students' Qur'an memorization ability through memorization submission, muroja'ah activities, and guidance from tahfidz teachers. However, the effectiveness of this program in enhancing students' memorization ability needs further investigation. This study aimed to determine the differences in Qur'an memorization ability between students participating in the Takhassus Al-Qur'an Program and those who did not participate in the program at MTsN 2 Pontianak. This study employed a quantitative approach with a comparative research design. The sample consisted of 53 students, including 24 students from the Takhassus Al-Qur'an Program and 29 regular students. Data were collected through tahfidz score documentation as the primary data and questionnaires as supporting data. Data were analyzed using the Shapiro-Wilk normality test, Levene's Test for homogeneity, and the Mann-Whitney U Test with the assistance of SPSS. The results indicated that both groups' data were not normally distributed and had unequal variances. The Mann-Whitney U Test yielded an Asymp. Sig. (2-tailed) value of 0.811 (>0.05), indicating that there was no significant difference in Qur'an memorization ability between students participating in the Takhassus Al-Qur'an Program and regular students. Therefore, the Takhassus Al-Qur'an Program has not shown a significant difference in improving students' Qur'an memorization ability at MTsN 2 Pontianak.